Transcutaneous tumor vaccination combined with anti-programmed death-1 monoclonal antibody treatment produces a synergistic antitumor effect. (1st March 2022) - Song, Xinran; Jiang, Yuxin; Zhang, Weixing; Elfawal, Gomaa; Wang, Kaili; Jiang, Di; Hong, Huoyan; Wu, Jinglei; He, Chuanglong; Mo, Xiumei; Wang, Hongsheng
Abstract: Transcutaneous immunization (TCI) has the advantages of safety, high efficiency, non-invasiveness and convenient use. The key for a TCI system is transdermal targeted delivery of antigen to dendritic cells (DCs), the most powerful antigen presenting cells. DCs also play an important role in tumor immunotherapy, which provides a huge imagination for the application of TCI to tumor treatment. In this study, a transcutaneous tumor vaccine (TTV) delivery system was developed using the electrospun silk fibroin (SF) and polyvinyl alcohol (PVA) composite nanofibrous patch loaded with mannosylated polyethyleneimine (PEI man )-modified ethosome (Eth) (termed Eth-PEI man ). Eth-PEI man showed a good performance in targeting DCs, and the carriers loaded with antigen (encapsulated in Eths) and adjuvant (absorbed in PEI man ) were observed effectively induce DCs maturation in vitro. With the tyrosinase-related protein-2 (TRP2) peptide as antigen and oligodeoxynucleotides containing unmethylated CpG motifs as adjuvant, the TTV-loaded patches (TTVP) significantly inhibited the growth of melanoma in a syngeneic mouse model for melanoma by subcutaneous injection of B16F10 cell lines. Moreover, the combined application of the TTVP and anti-programmed death-1 monoclonal antibody (aPD-1) produced a synergistic antitumor effect, which could be related to the infiltration of more CD4 + and CD8 + T cells in the tumor tissues. The application of TTVP also increased the expression of IL-12, which may be part of the mechanism of synergistic antitumor effect between the TTVP and aPD-1. These results suggest that the combination of the TTVP and immune checkpoint blockers could be an effective strategy for tumor treatment. Statement of significance: Transcutaneous immunization has the advantages of safety, high efficiency, non-invasiveness and convenient use. In this study, a novel transcutaneous tumor vaccine patch (TTVP) was developed using tumor antigens-loaded ethosomes that can target dendritic cells percutaneously. Our data demonstrated that the TTVP can significantly inhibit tumor growth. Furthermore, the combination of TTVP and aPD-1 produced a synergistic anti-melanoma effect. Considering its convenience and non-invasiveness, this TTVP system could find good application prospects in immunotherapy. The combination of TTVP and aPD-1 could be a useful strategy for the prevention and treatment of tumors. Graphical abstract: Image, graphical abstract